The Influence of the Work Environment and Work Discipline on the Performance of Bima City Population and Civil Registry Service Employees - Zhanirah Febriana; Jaenab, Jaenab; Julaiha, Julaiha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to determine the influence of the work environment and work discipline on employee performance at the Bima City Population and Civil Registration Service. The approach used is quantitative with an associative type of research. The sample in this study was 32 ASN employees selected using purposive sampling techniques. Data collection is carried out through observations, questionnaires and literature studies, with data analysis using multiple linear regression. The research results show that the work environment and work discipline have a significant effect both partially and simultaneously on employee performance. A determination coefficient value of 54.5% indicates that the two independent variables make a major contribution to employee performance. This finding shows the importance of creating a conducive work environment as well as implementing high work discipline in order to improve the performance of the civil service.